2012
DOI: 10.1590/s1516-35982012001000002
|View full text |Cite
|
Sign up to set email alerts
|

Intercropping of corn, brachiaria grass and leguminous plants: productivity, quality and composition of silages

Abstract: -The present study was carried out with the objective to evaluate the productive and qualitative characteristics of forages produced in systems of intercropping of corn, brachiaria grass and different leguminous plants. Productivity, bromatological composition and the fermentative profile of the silages from the following treatments were evaluated: corn in exclusive cultivation (CEC); intercropping of corn with brachiaria grass (CB); intercropping of corn, brachiaria grass and Calopogonium mucunoides (CBCal); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 10 publications
5
21
1
Order By: Relevance
“…The values are close to and sometimes within the parameters considered ideal for a silage of quality. Costa et al [6] found values of 7.0% to 11.8% lactic acid in the DM of the maize silage. Anil et al [41] evaluated maize silages with the addition of 30, 40 and 50% of soybean, and reported lactic acid values of 4.8; 5.0; and 5.1% in the DM, respectively.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…The values are close to and sometimes within the parameters considered ideal for a silage of quality. Costa et al [6] found values of 7.0% to 11.8% lactic acid in the DM of the maize silage. Anil et al [41] evaluated maize silages with the addition of 30, 40 and 50% of soybean, and reported lactic acid values of 4.8; 5.0; and 5.1% in the DM, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…The DM level was related to the fermentation conditions of the material [6]. DM yield characteristic is a very reliable parameter in agronomical studies [35].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations